MORPHOLOGICAL MEANS AND STYLISTICS: NOUN, ARTICLE, PRONOUN, ADJECTIVE, VERB - Qambarov , Shohruhbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This study explores the role of morphological means in stylistic expression in the English language, with a particular focus on nouns, articles, pronouns, adjectives, and verbs. Morphology, as a branch of linguistics, examines the structure and formation of words, while stylistics investigates how linguistic forms create expressive, emotional, and functional effects in discourse. The interaction between these two fields demonstrates how grammatical categories contribute not only to meaning but also to stylistic variation in different types of texts. Nouns serve as the primary carriers of conceptual information, while articles regulate definiteness and specificity, shaping the reader’s perception of reference. Pronouns enhance cohesion and reduce lexical repetition, contributing to textual economy and fluidity. Adjectives add descriptive depth and evaluative meaning, playing a crucial role in emotional coloring and imagery. Verbs, as dynamic elements, express actions, states, and processes, significantly influencing the tone and tempo of narration. The analysis shows that the deliberate use of these morphological categories allows authors to achieve stylistic richness, emphasis, and clarity. Understanding their stylistic functions is essential for both linguistic theory and practical language use, particularly in literary and academic writing.